A coordenação pedagógica em uma instituição de ensino superior: significações constituídas pelo coordenador pedagógico sobre o seu trabalho - Melo, Jucélia (2015)
This thesis aims to seize the meanings that the Educational Coordinator (EC) atributes to its activity in a HEI in São Paulo. As theoretical-methodological referential, the Socio- Historical Psychology was adopted, to Vigotski being its greatest representative, as well as the historical-dialectical method approach. The research is justified by the fact that in this HEI, the Educational Coordination has a differential role, since this professional is required only in Basic Education, by the law. In addition, he is the mediator between course coordinators, teachers and the institution in the development of educational policy of the HEI undergraduate courses. For data collection, an interview with the EC was made in two stages. After the speeches transcription, the analysis and interpretation of data was preceded, based on the proposal of Aguiar and Ozella (2006, 2013) on the Meaning Cores. In developing the proposal, four meaning cores were established: 1. The importance of the dialectical articulation theory and practice (praxis) as basis for the educational coordinating body activity; 2. The relevance of the Educational Coordinator experience while facilitator of activities with institutional authors; 3. Heterogeneity: the complexity in relationship of the Educational Coordinator with teachers and coordinators of different courses and areas; 4. Educational Coordinator: advisory team support, working conditions and course managers training policy. In closing considerations, an inter-core was made, which concludes that EC, subject of this research, is effectively an able mediator to articulate knowledge among teachers and coordinators. In his work, the importance of teaching practice and the relevance of their previous experience is highlighted, in addition to aspects of evident heterogeneity in relation to their peers, known positively. Special mention to his comment on the importance of institutional support as a facilitator element to the development of his work, besides the confidence atmosphere in which he develops himself. His vision as Coordinator goes beyond the activities that are inherent, as he believes that HEI could establish a course coordinators training policy through specialization or research groups in methodology area. EC expects the expansion of this sector, because it recognizes the importance of this activity as support and educational supervision of coordinators and teachers at HEI